Direct solar-to-hydrogen generation by quasi-artificial leaf approach: possibly scalable and economical device - Patra, Kshirodra Kumar; Bharad, Pradnya Arunrao; Jain, Vanshika; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2019)
Often, a disadvantage in one area of science may become an advantage in another area. In contrast, a successful concept in one area could work for a complementary area of research too. These two philosophies have been successfully used for solar hydrogen generation and they underscore the necessity to connect relevant concepts. We, herein, report a quasi-artificial leaf (QuAL) device in a wireless configuration with a TiO2/Mn-CdS composite and NiCu as a co-catalyst for possibly scalable as well as commercially viable solar hydrogen production under one sun conditions. The device works at no applied potential and generates 10.5 mL h(-1) (16 mL h(-1)) H-2 with Ni5Cu2.5 alloy (Pt) as a co-catalyst, which corresponds to a power conversion efficiency (PCE) of 4.8% (7.3%). The significant resemblance of NiCu alloy to Pt in terms of its electrochemical activity and electronic structure makes the device more economical. While the millisecond lifetime of electrons in Mn-CdS is known to help for white light emission, the same factor helps to greatly improve charge utilization for H-2 production in the QuAL device. In contrast, the reabsorption of emitted light is a vexing problem in emission applications; however in the present work, reabsorption is successfully utilized to enhance hydrogen yield. Spectroscopy techniques combined with electrocatalytic studies were employed and the results correlated with solar hydrogen generation, demonstrating this as a new pathway to design better solar-light-harvesting architectures.

Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.